Efficient and Scalable Enantioselective Synthesis of a Key Intermediate for Rimegepant: An Oral CGRP Receptor Antagonist - Luo, Zhonghua; Sun, Guodong; Wang, Guowei; Zhang, Xin; Zhang, Yang; Zhang, Ji (Pharmaceutical Fronts, 2024)
Rimegepant is a calcitonin gene-related peptide antagonist used for acute treatment and prevention of migraine. We herein attempt to explore an efficient and practiced method for scale-up, regio- and enantioselective synthesis of (R)-9-hydroxy-6,7,8,9-tetrahydro-5H-cyclohepta[b]pyridin-5-one (1), a key intermediate of rimegepant. In this work, a Ru-catalyzed asymmetric transfer hydrogenation (ATH) reaction was a key step. The optimization of the reaction conditions involved exploring the reaction parameters including catalysts, bases, and solvents. The results suggested that the Ru-catalyzed ATH process using formic acid as the hydrogen donor could be operated under mild conditions at a low catalyst loading (0.5 mol%), affording a high yield (92.1% yield with 99.8% purity) and gratifying enantioselectivity (99.9% ee) of the target product (1). This work first reported the Ru-catalyzed ATH process in the synthesis of key intermediates of rimegepant. The optimized ATH process was easy to implement and cost-effective, making it particularly suitable for manufacturing scale production.
Keywords: rimegepant; enantioselective synthesis; Ru-catalyzed; asymmetric transfer hydrogenation reaction